2011
DOI: 10.1159/000329466
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Results of Intravitreal Ranibizumab with or without Photodynamic Therapy for Polypoidal Choroidal Vasculopathy

Abstract: Purpose: To evaluate the safety and efficacy of intravitreal ranibizumab with or without photodynamic therapy (PDT) in the treatment of polypoidal choroidal vasculopathy (PCV) in Korean patients. Methods: A retrospective chart review of 22 patients (24 eyes) with PCV was conducted. Nine eyes were treated with intravitreal ranibizumab combined with a single session of PDT (group 1), and 15 eyes were treated only with ranibizumab (group 2). Such clinical evaluations as best-corrected Snellen visual acuity, centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…For example, the EVEREST study prospectively compared the 6-month outcomes of anti-VEGF monotherapy and combination therapy and found that the latter was statistically superior in terms of achieving complete polyp regression and reducing CRT, with no significant differences in visual acuity [32]. During a 12-month retrospective observation in another study, both combination therapy and monotherapy were found to improve visual acuity and reduce CRT, with no significant intergroup differences; additionally, fewer injections were required in the combination group [33]. As in these previous studies, the current study observed similar outcomes and a lack of adverse events with combination therapy and IAI monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the EVEREST study prospectively compared the 6-month outcomes of anti-VEGF monotherapy and combination therapy and found that the latter was statistically superior in terms of achieving complete polyp regression and reducing CRT, with no significant differences in visual acuity [32]. During a 12-month retrospective observation in another study, both combination therapy and monotherapy were found to improve visual acuity and reduce CRT, with no significant intergroup differences; additionally, fewer injections were required in the combination group [33]. As in these previous studies, the current study observed similar outcomes and a lack of adverse events with combination therapy and IAI monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results showed a significant increase in the mean BCVA in patients with tAMD, and a modest improvement in those with PCV. On the other hand, Song et al [25] reported that IVR without PDT for PCV in Korean patients resulted in visual and anatomical significant improvements over a 1-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that the polypoidal lesions of PCV were barely resolved by anti-VEGF monotherapy, which might explain the limited efficacy of IVR against PCV [138,139,140]. However, Song et al [141] reported that IVR without PDT for PCV in Korean patients resulted in significant visual and anatomical improvements over a 1-year follow-up period, and other reports suggested that the disappearance of the polypoidal lesions occurred at a high rate in PCV cases after anti-VEGF monotherapy [74,142,143]. A recent review suggested an overall improvement of the VA of PCV patients using IVR [144], and a most recent multicenter randomized controlled trial (LAPTOP study) revealed that IVR monotherapy achieved a significantly better visual prognosis than PDT monotherapy in PCV patients [145].…”
Section: Response To Treatmentmentioning
confidence: 99%